Intensified Effect of Adiposity on Blood Pressure in Overweight and Obese Children - Tu, Wanzhu (2011)
In children, blood pressure (BP) and risk for hypertension are proportional to degree of adiposity. Whether the relationship to BP is similar over the full range of adiposity is less clear. Subjects from a cohort study (n=1,111; 50% male and 42% black) contributed 9,102 semiannual BP and height/weight assessments. The mean enrollment age was 10.2 years and mean follow-up was 4.5 years. Adiposity was expressed as body mass index (BMI) percentile, which accounted for effects of age and sex. The following observations were made. The effect of relative adiposity on BP was minimal until the BMI percentile reached 85, beginning of the overweight category, at which point the effect of adiposity on BP increased by four-fold. Similarly intensified adiposity effects on BP were observed in children aged 10 or younger, 11 to 14 years, and 15 years or older. Serum levels of the adipose tissue-derived hormone, leptin, together with heart rate showed an almost identically patterned relation to BP to that of BMI percentile and BP thus implicating a possible mediating role for leptin. In conclusion, there is a marked intensification of the influence of adiposity on BP when children reach the categories of overweight and obese. Among the possible pathways, leptin may be a potentially important mediator acting through the sympathetic nervous system (reflected in heart rate). The findings have relevance to interventions designed to prevent or treat adiposity-related increases in BP and to the analytical approaches used in epidemiologic studies.